Attitudes of students of the College of Physical Education and Sports Sciences towards modern educational strategies used in scientific courses from the perspective of fourth-year students. - ياسر, الطائي; حمدان , عبدالله (Journal of Sport Science Technology and Physical Activities, 2025)
The aim of the research: To identify the trends of students of the College of Physical Education and Sports Sciences towards modern teaching methods. To determine the type of strategies used that students prefer in practical lessons. In light of the research results, the researcher adopted the descriptive method because it is appropriate for the study. The research community is represented by students of the College of Physical Education and Sports Sciences (fourth stage), amounting to (320) students. Conclusions: The research results indicate that students of the College of Physical Education and Sports Sciences have positive and strong attitudes towards using modern teaching methods, and they realize their reality in improving interaction and cognitive and skill achievement within practical lessons, and that students prefer specific educational strategies within the scientific educational environment, which is (Cooperative learning - project-based learning - flipped learning) which demonstrates their effectiveness and compatibility with good teaching methods in the field of physical education. Recommendations: - Work on using modern educational strategies in practical lessons, organizing educational programs and workshops for faculty members on how to use modern methods effectively in the practical education environment. Encouraging a culture of educational creativity among instructors by supporting the experimentation of modern educational strategies and motivating them to adopt them